2005
DOI: 10.1534/genetics.104.035642
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Diversity in Oryza sativa L.

Abstract: The population structure of domesticated species is influenced by the natural history of the populations of predomesticated ancestors, as well as by the breeding system and complexity of the breeding practices exercised by humans. Within Oryza sativa, there is an ancient and well-established divergence between the two major subspecies, indica and japonica, but finer levels of genetic structure are suggested by the breeding history. In this study, a sample of 234 accessions of rice was genotyped at 169 nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

95
808
19
31

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 995 publications
(953 citation statements)
references
References 43 publications
95
808
19
31
Order By: Relevance
“…Comparison of levels of diversity between wild and cultivated rice indicate that cultivated rice has a reduced subset of the total genetic variation of O. rufipogon; these results are consistent with other genetic studies on rice diversity (19). O. sativa cultivars, whether elite or landrace, share only a subset of haplotypes with O. rufipogon and are most often associated with tip positions in the gene networks ( Figs.…”
Section: Distribution Of Genetic Diversitysupporting
confidence: 89%
See 3 more Smart Citations
“…Comparison of levels of diversity between wild and cultivated rice indicate that cultivated rice has a reduced subset of the total genetic variation of O. rufipogon; these results are consistent with other genetic studies on rice diversity (19). O. sativa cultivars, whether elite or landrace, share only a subset of haplotypes with O. rufipogon and are most often associated with tip positions in the gene networks ( Figs.…”
Section: Distribution Of Genetic Diversitysupporting
confidence: 89%
“…With only a single sample of wild rice possessing haplotype C, the geographical origin of haplotype C is unclear. However, temperate japonica rice has been shown previously to be a subset of total japonica diversity and likely shares a common domestication event with the javanica rice sampled in haplotype B (19).…”
Section: Distribution Of Genetic Diversitymentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, monomorphism of the markers reflected genetic closeness of the cultivars. In closely related cultivars, these phenomena are frequent and are reported in many previous studies [22,[24][25][26]. However, comparatively high average PIC value (0.758) with a range from 0.511 to 0.861 that was calculated based on 51 polymorphic makers indicated that the cultivars are much diverged.…”
Section: Discussionmentioning
confidence: 71%